Analisis Potensi Halal Food Menggunakan Pendekatan Location Quotient Tahun 2015-2021 - Rosy Dwi Anita; Firsty Ramadhona Amalia Lubis; Lestari Sukarniati; Uswatun Khasanah (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2023)
This study aims to analyze the potential of halal food through the provision of food and beverages based on the GRDP of districts/cities in DIY in the period 2016-2021. The novelty that distinguishes this research from previous research is that there is no research that maps leading sectors to analyze the potential for halal tourism, especially halal food located in DIY. The type of data used is secondary data obtained from the Central Bureau of Statistics in the form of GRDP at constant prices for 2016-2021 for all regencies/cities in DIY. The method used is the Location Quotient (LQ) approach which provides an overview of the base and non-base sectors in an area. The results of the study show that the food and beverage supply sector from 4 regencies and 1 city shows that 2 regencies and 1 city are the base sector throughout 2016-2021. The areas in question are Sleman Regency, Yogya City, and Bantul Regency which are geographically located on one linear path. The potential for halal food in the three regions is reflected in the LQ value > 1 or is a leading sector and is supported by halal culinary maps in the three regions.